Campaign management of customer relationship management (CRM) / Lee Kar Kin - Lee, Kar Kin (2004)
Campaign Management is a management process on the campaign launched by the organizations when the want to promote their new products or new services to the marketplace. They do so with the expectation to capture as much attention as possible from the public on their promoted product or services through the launched campaign. Campaign can be launch d through multiple type of channels such as advertisement in mass or printed media etc. Since these kinds of campaign need much capital to be invested, so the investors' main purpose is to get back their Return-on-Investment (ROI) in the shortest period and generate revenue and profitability from the campaign. In this thesis. the Campaign Management System consists of four modules, which are Campaign Management Module, Lead Management Module, Customer Management Module and Campaign Analysis & Reporting Module. The functionalities in all of these modules include campaign planning, campaign management, response tracking, budget & revenue tracking, lead generation, lead dispatching, lead distribution, customer profiling, campaign performance analysis, reporting etc. As for development environment, ASP.NET and VB.NET have been chosen as the application language, and hence, .NET Framework automatically becomes the chosen framework. Meanwhile, SQL Server is chosen as the Database Management System; Internet Information Services (IIS) as the web server and Active Data Object, or ADO.NET as the data access technology. As overall, there will a high expectation that this system can be designed to be the user friendly system, with sophisticated graphical representation on data mining and high sensory of critical information, like campaign progress, budget, generated revenue, lead status etc. Hopefully, these features might help some of the small- and medium-sized companies to effectively and efficiently handle their campaign, and hence maximize their ROI and revenue in the shortest period.